Diskursus Intiqalul Al-Madzab Dalam Ibadah Wukuf: Kajian Komparatif Pada Buku Al-Fiqh ‘Ala Al-Madzahib Al-Arba’ah dan Al-Fiqh Al-Islami Wa Adillatuhu - Gusmiarni, Alfina; Muhajarah, Kurnia; Rozaq, Abdul; Hasanah, Hasyim; Darissurayya, Vina (Jayapangus Press, 2025)
This research discusses the discourse on shifting madhhabs (intiqalul madhhab) in the context of wukuf based on two seminal works in Islamic jurisprudence: al-Fiqh ‘ala al-Madhāhib al-Arba‘ah by Abdulrahman al-Juzairi and al-Fiqh al-Islāmī wa Adillatuhu by Wahbah az-Zuhaili. The diversity of legal interpretations among the four major Sunni madhhabs (Hanafi, Maliki, Shafi‘i, and Hanbali) has made the issue of switching madhhabs a relevant topic, particularly in pilgrimage rituals like wukuf, where the validity of worship can depend on specific legal requirements. This research aims to analyze how both scholars frame the concept of intiqāl al-madhhab, and to evaluate its relevance to contemporary hajj practices. The study employs a qualitative method with a library research approach, using descriptive-comparative analysis of both texts to explore methodological similarities and differences. The findings reveal that both works support the legitimacy of madhhab transition under certain shar‘i conditions. Al-Juzairi emphasizes the comparative diversity of fiqh rulings and presents detailed mazhab-based legal options for wukuf. Az-Zuhaili, on the other hand, strengthens this flexibility through in-depth textual analysis and the application of maqāṣid al-sharī‘ah. The study concludes that shifting madhhabs can serve as a practical and theologically grounded solution for pilgrims facing complex or difficult situations. This aligns with the Islamic legal maxims promoting ease and removing hardship, making intiqāl al-madhhab a valid contemporary approach in ritual practice.